The significance of differential advantage / Dr. Norhidayah Ali, Azni Syafena Andin Salamat and Suhaida Abu Bakar - Ali, Norhidayah; Andin Salamat, Azni Syafena; Abu Bakar, Suhaida (Universiti Teknologi MARA, Kedah, 2023)
The fierce competition in today’s business landscape has driven many companies to take serious measures to win customers in order to perform and sustain in the long term. Some are looking at ways to be different yet advantageous relative to their competitors. The term differential advantage, or also known as competitive advantage, has been used by academicians and practitioners to portray companies that differentiate themselves and stand out amongst their competitors. With the emergence of differential advantage, it has become a challenge for organisations to revise their business strategy over a period of time. Organisations can build greater customer satisfaction and loyalty by understanding and developing differential advantages. The strategies adopted need to be accompanied with high-quality products or services, intellectual property, brand identity, and pricing and marketing efforts, among others.